Restoration of posterior teeth using occlusal matrix technique - Martos Josue; Silveira Luiz Fernando; Ferrer-Luque Carmen; González-López Santiago (Indian Journal of Dental Research, 2010)
This article describes a technique for duplicating occlusal surface anatomy using the Biteperf device. Duplication requires an intact occlusal enamel surface and is only indicated when caries lesions are hidden. The occlusal matrix technique allows for preservation of all anatomic details. When the last layer of composite has been placed, the occlusal matrix is forced into the uncured composite to replicate the original occlusal surface, instead of performing manual curing and shaping as in the standard approach. It is technically possible to achieve this effect with any material that is able to copy anatomic details. The main benefits of the occlusal matrix technique, more precisely the Biteperf, are the technical ease of use due to its simplicity and its high accuracy in reconstructing occlusal morphology.